Pengaruh Media Interaktif Animasi Terhadap Minat Belajar Siswa Pada Mata Pelajaran IPA Siswa Kelas V UPT SPF SD Negeri Kalukuang II Makassar - Asmayani Asmayani; Nasrah Nasrah; Nurul Magfirah (Departement of Mathematics Education, 2023)
The purpose of this study is whether interactive animated media in science learning can influence the learning interest of fifth grade students at UPT SPF Negeri Kalukuang II Makassar. This study aims to determine whether there is an influence of interactive animated media in science learning on students' learning interest in class V UPT SPF Negeri Kalukuang II Makassar. This study uses a type of quantitative research with pre-experimental methods with the One Group Pretest and Posttest Design model. With the number of population and sample, namely class V with a total of 25 students. Data collection methods used questionnaires and documentation. The data analysis technique used is descriptive statistical analysis techniques and inferential statistics. The results showed that the average student pretest result was 78.5 in the less category, then interactive animated media was applied to the learning process so that the posttest results of students achieved an average score of 89.65 in the High category. Based on the hypothesis test using the paired samples test obtained in the management of the Sig. (2-tailed) < α then obtained 0.001 < 0.05. This shows that H0 is rejected and H1 is accepted. In addition, it can also be seen from the average pretest result of 78.5 with the highest score of 74 and the lowest score of 44, while the average posttest result is 89.65 with the highest score of 91 and the lowest score of 56. N-Gain analysis shows the average normalized gain of 0.457 is in the medium category. From these results it can be concluded that there is an influence of interactive animated media on students' learning interest in Science lessons for Class V SD Negeri Kalukuang II Makassar.